THE ROLE OF SCHOOL PRINCIPAL AND SCHOOL SUPERVISORS IN IMPROVING TEACHER COMPETENCY IN THE APPLICATION OF LEADING SAINTIFIC APPROACH IN VOCATIONAL HIGH SCHOOL - Purwanto, Djandji (Jurnal Aplikasi Manajemen, 2017)
The purpose of this study examines the role of School Principal and school supervisors in improving teacher competence. The population in this study are teachers of Vocational High School in Malang City consisting of 20 vocational schools as many as 1488 teachers, with a sample of 94 teachers. The analysis used is multiple regression. The results showed that the role of the school principal and the role of school supervisors has a significant relationship with teacher competence. The Principal of Vocational High School in Malang City, always share the knowledge that has been obtained in the world of teaching to the teachers and improve the quality of leadership especially in supervising to improve the professional competence of teachers and teachers should be more active in following the training activities, so that the training they follow can really be useful and increase their professional competence.